1992
DOI: 10.1177/088626092007003002
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Family Background to the Long-Term Adjustment of Women Sexually Abused as Children

Abstract: The current study tested the relative influence of relationship variables in the family of origin and sexual abuse characteristics in predicting the long-term adjustment of child sexual abuse survivors. A total of 103 subjects, 45 of whom had histories of sexual abuse, completed self-report measures of perceived parental conflict, paternal dominance, current psychological distress, social support and dyadic relationships, and a questionnaire on their experiences of childhood sexual abuse. Persons with historie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 22 publications
3
32
0
1
Order By: Relevance
“…The same pattern was found regarding authoritarian mother and father parenting styles. These findings are in accordance with the literature about childhood EA that has been linked with, for example, parenting domination and control; that is, authoritarian parenting style in this study (Edwards & Alexander, 1992).…”
Section: Discussionsupporting
confidence: 94%
“…The same pattern was found regarding authoritarian mother and father parenting styles. These findings are in accordance with the literature about childhood EA that has been linked with, for example, parenting domination and control; that is, authoritarian parenting style in this study (Edwards & Alexander, 1992).…”
Section: Discussionsupporting
confidence: 94%
“…Satisfaction with male intimate partner relations. Women with a history of sexual abuse are said to experience a set of intensely ambivalent feelings (e.g., disillusionment, mistrust, idealization, devaluation, and hostility) about men in general (Briere, 1996), and compared to nonabused women, survivors may experience less satisfaction in platonic interactions with males (Edwards & Alexander, 1992). Numerous clinical writings have documented patterns of dysfunction in survivors' marital and couple relationships (Courtois, 1988;Kirschner et al, 1993;Maltz & Holman, 1987;Meiselman, 1990).…”
Section: Couple Relationshipsmentioning
confidence: 99%
“…There have also been important recent discussions within the field of child maltreatment about the extent to which child maltreatment itself is responsible for longterm negative consequences and the extent to which such effects may be driven by the broader context of family dysfunction that often surrounds experiences of abusẽ Alexander, 1992;Banyard, Arnold, & Smith, 2000;Edwards & Alexander, 1992;Romans, Martin, Anderson, O'Shea, & Mullen, 1995;Wind & Silvern, 1994;Yama, Tovey, & Fogas, 1993!. These studies have generally found that abuse survivors report more negative family relationships than nonabused samples but have been mixed about the extent to which negative family environment mediates the relationship between abuse and outcomes.…”
Section: Understanding Trauma and Powermentioning
confidence: 93%